KONSTRUKSI KALIMAT TRANSITIF BAHASA MELAYU KUPANG ( KAJIAN TATABAHASA LEKSIKAL FUNGSIONAL) - Agnes Maria Diana Rafael; Darius Y Nama (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2022)
Abstract. Kupang Malay is a language that belongs to Malay language family. Typologically, the morphology of Kupang Malay is classified as agglutinating language, which is a language that has a morpholexical process. This study aims to examine the construction of Kupang Malay transitive sentences using functional lexical grammar studies. The research method used is descriptive-qualitative method, because it is considered capable of providing a systematic, accurate, and factual explanation of the data, properties and relationships of the phenomena studied and ultimately produces a scientific picture of the data (Djajasudarma, 1993:8) . The types of data collected and analyzed in this study were all oral data sourced from informants who were Kupang Malay native speakers. This study used the equivalent analysis method and the agih method. The results of the research concluded that the transitive sentence construction of Kupang Malay consists of an intransitive verb clause and a ditransitive verb clause. For example, in transitive verbs the number 'angka' there is the only OBJ in the grammatical relation, which is present as the main argument needed by a verb other than SUBJ in each verb. Kupang Malay's transitive clause structure with numeric verbs as the core of the clause occupies the predicate position, so that the verb must be present unmarked or is a verb without affixes. Furthermore, the second type of transitive verb is contained in a ditransitive clause. The ditransitive verb has three main arguments in grammatical functions as SUBJ, OBJ, and OBJɵ.